Comparative analysis of direct, diffuse and global Irradiance at two different locations in Nepal - Maharjan, Arbin; Maharjan, Kabina (Journal of Advanced College of Engineering and Management, 2026)
Analysis of solar radiation on different geographical location is important to understand their solar potential and possible energy harvest that can be turned to financial benefits for investors. Nepal has a huge solar potential but large scale solar installations are still minimal. In this regard, this study is an attempt to compare solar irradiances of two different geographical locations (Kathmandu & Nepalgunj) to observe the possible energy output. Real ground measurements of global and diffuse horizontal irradiances (GHI and DHI) along with direct normal irradiance (DNI) data are obtained for six months (Jan to June, 2019) from both sites. Analysis is presented based on comparison of daily and monthly average irradiances along with min by min plot of GHI for particular day of winter and summer season. Results suggest that average daily and monthly irradiance (GHI and DNI) for four out of six months (March toJune) are higher in Nepalgunj as compared to Kathmandu. The six month averages of GHI=350.38 W/m2 and DNI=296.51 W/m2 in Nepalgunj are found to be slightly higher than that of Kathmandu (GHI=321.9 W/m2, DNI=292.25 W/m2). Both locations have very good sunshine of 5 hours/day in winter and excellent sunshine of 8 hours/day in summer. Also during summer, the average GHI greater than 500 W/m2 that would generate more energy output from the solar collector is higher for Nepalgunj ( 71%) as compared to Kathmandu ( 50%) whereas during winter, it is nearly 60% in Kathmandu and only about 39% in Nepalgunj.